Clinical Ultrasound A Pocket Manual - Creditt, Angela (Springer International Publishing, 2018)
This pocket manual is designed to guide medical professionals in acquiring skills in basic ultrasound imaging. It describes the most common scans performed at the patient's bedside, specifically in the emergency department or intensive care unit. Following an overview of basic ultrasound principles, the use of this modality to visualize specific organ systems is described. In a quick-reference bulleted format, each chapter details indications, basic techniques (patient position, organ windows/views), probe placement, anatomy, pathology, pearls, and key points in ultrasound imaging. The extensive collection of images helps orient the reader in interpreting the scans, depicts anatomic landmarks, and identifies key pathologic findings for each organ system. Clinical Ultrasound: A Pocket Manual is an accessible guide to performing bedside ultrasound imaging for emergency medicine physicians, primary care physicians, critical care medicine providers, residents, and medical students. .